Learning from local knowledge on changes in tree-cover and water availability: the case of the contested agroforested landscape of the Mt. Elgon Water Tower, Uganda - Kimbowa, George; Buyinza, Joel; Gathenya, John M.; Muthuri, Catherine (Frontiers in Water, 2024)
i.Tree cover change follows different patterns across the two altitudinal zones in both RiverManafwa and Sipi River sub-catchments.ii. Key experts perceived a decrease in overall tree cover and in natural forest cover during the 1990-2020 period.iii.Households selected from River Manafwa and Sipi River sub-catchments perceived that during 2006-2020 period, water availability in their catchments had increased and decreased respectively.iv. Differences between two zones for 2006-2020 water availability were noticeable in both RiverManafwa and Sipi River sub-catchments v.Since 2006, average monthly precipitation has increased and decreased in River Manafwa and Sipi River sub-catchments respectively corresponding with FGD exercise findings.